Kepemimpinan Transformasional sebagai Pendekatan Pengelolaan Sumber Daya Manusia: Tinjauan Literatur - Mely Nur Ratman; Nasya Handini; Suci Oktapia; Nisa Nur Amanda; Wahjoe Pangestoeti (CV. ITTC INDONESIA, 2025)
Transformational leadership has proven to be an effective approach to human resource (HR) management in various organizations, including the public sector. This study discusses how transformational leaders can inspire, motivate, and empower employees to transcend personal interests for the greater good of the organization. With an approach based on inspiring vision, intellectual stimulation, and individual attention, transformational leadership supports employee competency development and empowerment, which in turn improves organizational performance. However, the implementation of transformational leadership in public organizations faces challenges such as resistance to change, limited resources, and rigid bureaucratic structures. Therefore, this study recommends inclusive policies that support the development of transformational leadership and collaboration between agencies, as well as providing continuous feedback as an effort to overcome existing obstacles.